Mitoni sebagai Tradisi Budaya dalam Masyarakat Jawa - Fitri Nuraisyah; Hudaidah Hudaidah (Historia Madania: Jurnal Ilmu Sejarah, 2021)
This article discusses the Javanese tradition in the form of mitoni, the writing of this article aims to analyze the mitoni tradition carried out by people in Java, starting from the preparation before carrying out the mitoni tradition ceremony to the stage of implementing the mitoni tradition. The method used in writing this article is a literature study which is used as a source of data taken from journals and digital books, besides that the data collection technique also uses interview techniques conducted to actors who have carried out the mitoni tradition. The result of writing an article is in the form of a tradition which means that it is a habit that is carried out from the ancestors and then passed on from generation to generation from one generation to the next. In this article, we discuss the mitoni tradition. Mitoni is a tradition carried out by the Javanese people when a mother is pregnant with her first child at the age of seven months. This mitoni tradition usually includes the preparation of tools and materials before carrying out the mitoni tradition ritual, then doing the mitoni tradition starting from the bathing stage, splitting coconut ivory, changing seven kinds of cloth, selling dawet ice and rujak. Then when bathing, the dipper used is made of coconut shell. Furthermore, this article also discusses the meaning of the mitoni tradition which is also called tingkeban.